2020
DOI: 10.1007/s40037-020-00565-5
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, skills and beetles: respecting the privacy of private experiences in medical education

Abstract: In medical education, we assess knowledge, skills, and a third category usually called values or attitudes. While knowledge and skills can be assessed, this third category consists of 'beetles', after the philosopher Wittgenstein's beetle-in-a-box analogy. The analogy demonstrates that private experiences such as pain and hunger are inaccessible to the public, and that we cannot know whether we all experience them in the same way. In this paper, we claim that unlike knowledge and skills, private experiences of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(32 citation statements)
references
References 17 publications
0
25
0
Order By: Relevance
“…Some have gone so far as to even argue that the measurement of individual empathy is unknowable. 54 The uncertainties around educational interventions to promote empathy only expand with a longer frame of reference. According to recent reviews, many interventions have only shown temporary effectiveness.…”
Section: Empathy Measurementsmentioning
confidence: 99%
“…Some have gone so far as to even argue that the measurement of individual empathy is unknowable. 54 The uncertainties around educational interventions to promote empathy only expand with a longer frame of reference. According to recent reviews, many interventions have only shown temporary effectiveness.…”
Section: Empathy Measurementsmentioning
confidence: 99%
“…No matter how valid the scales might be, though, only a trained observer can determine whether those skills and qualities are applied appropriately and ethically-does this student not only know the words of empathy, but also apply them at the right moment, and equitably? There is no substitute for careful observation, both in real or simulated environments, and by their very nature, assessments based on careful observation are always intersubjective, contextual and evolving [11]. Outcomes also have to be clearly defined, and realistic.…”
mentioning
confidence: 99%
“…In the case of OSCEs, educators may reconsider the utility of assessing ‘shows’ and ‘performances’ of empathy, for ‘show’ and ‘performance’ is precisely the level the OSCE occupies in Miller's pyramid 53 . Educators who regard empathy as a ‘way of being’ 8 are more likely to recognise that the mere show of compassion does not equate to the true act, and would reject an assessment that confuses the two 54 . If empathy is to be assessed at all, our preference would be real‐world clinical placement judgments made by tutors, as suggested by students in this study.…”
Section: Discussionmentioning
confidence: 99%